A bibliometric analysis on research trends of outcome-based education in higher education - Tsaniya Sholihah; Riche Cynthia Johan; Gema Rullyana (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study aims to determine the trend of research on learning outcome-based education implemented in higher education that is published. An overview of these research trends can be the basis for determining the focus of research that can be carried out related to learning outcomes-based education to improve the quality of higher education implementation. This research uses a bibliometric analysis method of 140 published research documents from the Scopus database. This research begins by collecting documents discussing learning outcomes-based education in Higher Education. Then, we analyzed the results using VOSviewer software to visualize all documents' keyword and author linkage maps. The results of the analysis show that the number of publications on learning outcome-based education in higher education tends to increase yearly. The three highest countries in the number of publications on learning outcome-based education in higher education are India, Malaysia, and the Philippines. Indonesia needs to increase research in this field to optimize the implementation of outcome-based learning in higher education. Abstrak Penelitian ini bertujuan untuk mengetahui tren penelitian mengenai pendidikan berbasis capaian pembelajaran yang dilaksanakan di pendidikan tinggi yang dipublikasikan. Gambaran mengenai tren penelitian tersebut dapat menjadi dasar menentukan fokus penelitian yang dapat dilakukan terkait pendidikan berbasis capaian pembelajaran untuk meningkatkan kualitas pelaksanaan pendidikan tinggi. Penelitian ini menggunakan metode analisis bibliometrik terhadap 140 dokumen penelitian yang telah dipublikasi bersumber dari database Scopus. Penelitian ini diawali dengan mengumpulkan dokumen penelitian yang membahas pendidikan berbasis capaian pembelajaran di Pendidikan Tinggi. Kemudian kami analisis menggunakan perangkat lunak VOSviewer untuk memvisualisasikan peta keterhubungan kata kunci dan penulis dari seluruh dokumen. Hasil analisis menunjukkan jumlah publikasi mengenai pendidikan berbasis capaian pembelajaran di pendidikan tinggi cenderung meningkat di setiap tahunnya. Tiga negara tertinggi dalam jumlah publikasi mengenai pendidikan berbasis capaian pembelajaran di pendidikan tinggi adalah India, Malaysia, dan Filipina. Indonesia perlu meningkatkan penelitian mengenai bidang ini sebagai salah satu upaya mengoptimalkan pelaksanaan pendidikan berbasis capaian pembelajaran di pendidikan tinggi. Kata Kunci: analisis bibliometrik; pendidikan berbasis capaian pembelajaran; pendidikan tinggi